أثر التسويق الرقمي على رضاء الزبون دراسة ميدانية بالوكالة التجارية موبيليس عنابة" - جمال جوامع; سناء مباركي (My University, 2022)
This research aims to identify the concepts surrounding digital marketing as one of the modern directives for marketing and its impact on customer satisfaction, by studying the impact of digital marketing and its tools on customer satisfaction. In order to achieve this, a questionnaire consisting of 27 paragraphs was used distributed among a sample of 46 customers at the Mobles commercial agency in Annaba. And he used the statistical package for the social sciences (SPSS) program to analyze the data and test the study hypotheses. The study proved that digital marketing has an impact on customer satisfaction. ........................................ يهدف هذا البحث إلى التعرف على المفاهيم المحيطة بالتسويق الرقمي كأحد التوجيهات الحديثة للتسويق وأثره على رضا الزبائن الوكالة التجارية موبليس وذلك من خلال دراسة اثر التسويق الرقمي على رضا الزبون ومن اجل تحقيق ذلك ، تم استخدام استبانه مؤلفة من 27 فقرة موزعة على عينة تتكونة 46 زبون لدى الوكالة التجارية موبليس بمدينة عنابة . وقام باستخدام برنامج الحزم الاحضائية للعلوم الاجتماعية spss من اجل التحليل المعطيات واختبار فروض الدراسة . أثبتت الدراسة أن التسويق الرقمي له تأثير على رضا الزبائن.